An Energy-Based Similarity Measure for Time Series. (18th November 2007) - Boudraa Boudraa, Abdel-Ouahab Abdel-Ouahab; Cexus Cexus, Jean-Christophe Jean-Christophe; Groussat Groussat, Mathieu Mathieu; Brunagel Brunagel, Pierre Pierre
Abstract : A new similarity measure, called SimilB, for time series analysis, based on the cross-Ψ B -energy operator (2004), is introduced.Ψ B is a nonlinear measure which quantifies the interaction between two time series. Compared to Euclidean distance (ED) or the Pearson correlation coefficient (CC), SimilB includes the temporal information and relative changes of the time series using the first and second derivatives of the time series. SimilB is well suited for both nonstationary and stationary time series and particularly those presenting discontinuities. Some new properties ofΨ B are presented. Particularly, we show thatΨ B as similarity measure is robust to both scale and time shift. SimilB is illustrated with synthetic time series and an artificial dataset and compared to the CC and the ED measures.